PENGARUH PERLAKUAN 3 JENIS BAKTERI ASAM LAKTAT DAN KOMBINASINYA TERHADAP KARAKTERISTIK KEJU KEDELAI - ., Nurgrahadi; Puspawati, Ni Nyoman; Sugitha, I Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 4 (2020): Jurnal ITEPA, 2020)
The aims of this research was to determine the effect of using 3 different types of lactic acid bacteria and their combinations for the characteristics of soy cheese. This research used a Completely Randomized Design (CRD) with 7 treatments, namely Lactobacillus bulgaricus, Lactococcus lactis and Lactobacillus paracasei spp. paracasei 1 SKG44, which is a single starter, and several combinations consisting of L. bulgaricus with L. lactis; L. bulgaricus with L. paracasei spp. paracasei 1 SKG44; L. lactis with L. paracasei spp. paracasei 1 SKG44; and L. bulgaricus, L. lactis, and L. paracasei spp. paracasei 1 SKG44. The concentration of each treatment was 6%. The treatment was repeated 3 times to make 21 experimental units. The data was obtained by variance analysis and if there was an influence between treatments continued with the Duncan test. The results showed that the addition of different starter combinations would affected the characteristic of soy cheese. The combination treatment of L. bulgaricus, L. lactis, and L. paracasei spp. paracasei 1 SKG44 was produced the best soy cheese with a yield of 27,47%; 17, 02% protein content; 4,1 x 107 CFU/g total LAB; 0,13% total lactic acid; 79,10% moisture content; color rather white; texture soft; aroma rather typical of soybeans, flavor rather like and overall acceptance like.